The influence of financial literacy and financial inclusion on MSME performance in Pati Regency - Dito Mahardani; Hikmah Hikmah; Janti Soegiastuti; Nurchayati Nurchayati (International Journal of Applied Finance and Business Studies, 2026)
This study seeks to examine the impact of financial literacy and financial inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Pati Regency. In this study, financial literacy and financial inclusion are the independent variables, and MSME performance is the dependent variable, assessed by measures of profit, marketing area, workforce, and capital. The study employs a quantitative methodology via a survey approach and data collecting via questionnaires administered to 100 MSME participants in Pati Regency. We utilized SPSS version 27 software to do multiple linear regression on the data. The findings indicate that financial literacy positively and significantly influences MSME performance in Pati Regency. This means that better understanding and better money management can help a business do better. Moreover, financial inclusion positively and significantly impacts MSME performance, underscoring the importance of access to and utilization of formal financial services in fostering MSME development. The adjusted R-square value of 13.6% indicates that the variables of financial literacy and financial inclusion can account for some of the differences in MSME performance, while other factors account for the rest.